Binding agents for low-salt, low-fat, restructured beef roasts: connective tissue or gelatin - P.B. Kenney; Donald H. Kropf; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 1991)
Connective tissue, from the outside of three major chuck muscles, was evaluated for binding properties when incorporated either raw or following preheating into precooked, restructured beef. Food-grade gelatin was also evaluated as a binding agent. Adding 10% raw or preheated connective tissue increased (P<.05) instrumentally measured tensile strength and reduced (P<.05) juiciness perception. One percent gelatin reduced (P<.05) cook yields and increased (P<.05) tensile strength but not to the degree of 10% raw or preheated connective tissue. Preheating had minimal effects on improving connective tissue utility. Based on the improvement in bind and cook yields, use of connective tissue as a binder is feasible in manufacturing low-salt, precooked, restructured beef.
Keywords: Cattlemen& #x27; s Day; 1991; Kansas Agricultural Experiment Station contribution; no. 91-355-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 623; Beef; Restructured beef; Connective tissue; Gelatin; Tensile strength